2013
DOI: 10.4103/0253-7613.117778
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the protective role of α-tocopherol on free radical induced hepatotoxicity and nephrotoxicity due to chromium in rats

Abstract: Aim:To avert the health problems induced by many environmental pollutants, available antioxidants have been evaluated. The present study was aimed to investigate whether α-tocopherol could protect the hexavalent chromium (Cr VI)-induced peroxidation in the liver and kidney and to explore the underlying mechanism of the same.Materials and Methods:A total of 24 Wistar adult female rats were equally divided into four groups. Group 1 served as control while Groups 2 and 3 were administered K2Cr2O7(10 mg/kg b.wt. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 24 publications
1
14
0
4
Order By: Relevance
“…The results of the present study demonstrated that Cr (VI) produced dose–dependent adverse effects on rat kidney. Nephrotoxicity of Cr (VI) was reported by several investigators (1-5). Our findings along with others suggested that kidney is susceptible for Cr (VI)-induced toxicity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results of the present study demonstrated that Cr (VI) produced dose–dependent adverse effects on rat kidney. Nephrotoxicity of Cr (VI) was reported by several investigators (1-5). Our findings along with others suggested that kidney is susceptible for Cr (VI)-induced toxicity.…”
Section: Discussionmentioning
confidence: 95%
“…Sahu et al found that subcutaneous injection of chromium (VI) resulted in histopathological alterations in the rat kidney (4). Balakrishnan et al reported that administration of chromium in rats significantly reduced the antioxidant markers such as superoxide dismutase and reduced glutathione (GSH) along with significant increase in peroxidation markers such as malondialdehyde (MDA) in the rat kidney as compared with control animals (5). Khan et al exhibited Cr (VI) produced injury in rat kidney (6).…”
Section: Introductionmentioning
confidence: 99%
“…The lipid peroxidation (LPO) produced by hydrogen peroxide, superoxide anion and hydroxyl radicals which result in altered structural integrity of cell membrane, cell organelle and loss of essential fatty acids by the formation of peroxide products 27 . The increased kidney oxalate concentration in EG treated groups of animals shown to inhibit the catalase activity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…За тривалого надходження Cr(VI) з повітрям і питною водою відбувається порушення функцій дихальної, травної, видільної, кістково-м'язової, нервової та імунної систем, збільшується ризик розвитку злоякісних пухлин та пригнічення процесів ембріонального розвитку [4]. Відомо, що під час поступового відновлення Cr(VI) до Cr(ІІI) індукується оксидативний стрес, шляхом стимулювання продукції АФО, а накопичення продуктів вільнорадикальних реакцій викликає пригнічення функціональної активності антиоксидантної системи, зумовлюючи зміщення рівноваги в системі прооксиданти-антиоксиданти [5,6].…”
Section: Buchko_oksana@ukrnetunclassified